Media Online dan Biodigilib sebagai Solusi Peningkatan Layanan Perpustakaan - Setiawan, Aris (Media Informasi, 2024)
Limited physical contact which was initially caused by the COVID-19 pandemic at the beginning of 2020 resulted in The library having temporarily closed its services. The library as an institution which has the task of managing collections professionally using a standard system to meet the educational, research, preservation and recreation needs of its users must make changes. This research aims to determine the benefits of online media and digital libraries to improve library services. The method used is literature study and observation of the YouTube and Biodigilib applications. Online media is a technology product that can be used as a means of information and also a communication tool to improve library services. The ease of use of social media (Youtube) can be implemented and used in libraries, both to promote collections and information held by libraries or as a medium of communication between libraries and users. The Biodigilib digital library application is the result of technology, this application cannot replace 100% of conventional libraries. Digital libraries can be used as a hybrid library service as a companion. These two technological results, namely online media (Youtube) and the biodigilib application, can be used as a solution in libraries if there is limited physical contact.